Potential effects of expansion of the panama canal on midwest Brazilian soybean logistics - Renato de Palma Llorca; Harlenn dos Santos Lopes; Renato da Silva Lima (Logistics Research, 2020)
This work analyzed the potential impact on the soybean outflow Logistics from Brazilian Midwest to China caused by the Panama Canal expansion, completed in 2016. Scenarios were built out to analyze the use of this route in compare to the traditional route, which skirts the Cape of Good Hope. A mathematical optimization model based on Linear Programming was constructed using the transportation problem, considering the main soybean exporting ports, Brazilian internal logistic infrastructure and new projects to optimize logistics costs. In 2017, there was a low influence of Panama Canal on the soybean transportation between Brazil and China. However, the growth of exported soybean projections aims to the huge potential for demand to export through the North ports, due to their geographical locations, closer to the producing areas, capacity constraints in Brazilians Southern ports and new investments in Brazilian infrastructure, increasing the competitiveness of the route via the Panama Canal.
Keywords: 650; Logistics; Brazilian Soybean; Panama Canal; Costs; Operational Research